PEMILIHAN UMUM DALAM SISTEM DEMOKRASI PRESPEKTIF SILA KE- 4 PANCASILA - Yusuf Eko Nahudin (Jurnal Cakrawala Hukum, 2017)
Elections are a manifestation of democracy reflecting the fourth principle of Pancasila. Elections that prioritize the dialogical approach of vision and mission as a solution to the nation’s problems undertaken by election participants who truly reflect the soul-bearing souls of Pancasila. Selected individuals who meet the criteria of lection are credibility, integrity and acceptability as well as popolarity due to achievement, dedication and loyalty to the nation and country that are worthy to lead this country. The development of many election participants who can not reflect the value of democracy according to the 4th principle of Pancasila. The method used is normative with the approach of norms and existing theories reviewed to solve the issues raised. The use of political parties plays a major role in creating elections that reflect the value of Pancasila. Pancasila is the foundation of the nation’s philosophy is the root of life of the nation of Indonesia in carrying out its life must always be held firm. General election merupkan form of democracy that berprespektif Pancasila to seek leaders of noble personality who practice Pancasila so as to bring progress and prosperity of the nation and state of Indonesia.DOI: https://doi.org/10.26905/idjch.v8i2.1670